Fibro–Adipogenic Progenitors Cross-Talk in Skeletal Muscle: The Social Network - Biferali, Beatrice; Proietti, Daisy; Mozzetta, Chiara; Madaro, Luca (Frontiers in Physiology, 2019)
Skeletal muscle is composed of a large and heterogenous assortment of cell populations that interact with each other to maintain muscle homeostasis and orchestrate regeneration. Although Satellite Cells (SCs) - which are muscle stem cells - are the protagonists of functional muscle repair following damage, several other cells such as inflammatory, vascular and mesenchymal cells coordinate muscle regeneration in a finely tuned process. Fibro-Adipogenic Progenitors (FAPs) are a muscle interstitial mesenchymal cell population, which supports SCs differentiation during tissue regeneration. During the first days following muscle injury FAPs undergo massive expansion, which is followed by their macrophage-mediated clearance and the re-establishment of their steady state pool. It is during this critical time window that FAPs, together with the other cellular components of the muscle stem cell niche, establish a dynamic network of interactions that culminate in muscle repair. A number of different molecules have been recently identified as important mediators of this cross-talk, and its alteration has been associated with different muscle pathologies. In this review, we will focus on the soluble factors that regulate FAPs activity, highlighting their roles in orchestrating the inter-cellular interactions between FAPs and the other cell populations that participate in muscle regeneration.